Discretization and Asymptotic Normality of Drift Parameters Estimator in the Cox-Ingersoll-Ross Model - Olha Prykhodko; Kostiantyn Ralchenko (Austrian Journal of Statistics)
This paper investigates the simultaneous estimation of two drift parameters of a Cox-Ingersoll-Ross (CIR) model, for which observations can be made either continuously or at discrete time instants. For continuous-time observations, we establish the joint asymptotic normality of the strongly consistent parameter estimators introduced in Dehtiar et al. (Comm. Statist. Theory Methods, 51(19):6818–6833, 2022). Additionally, we study the discrete counterparts of these estimators and prove their strong consistency and joint asymptotic normality.